WHAT IS ACCOUNTING? - Raun, Donald L. (The Accounting Review, 1962)
The article focuses on the definition of accounting. The author states that to the advanced accounting student or practicing accountant, the art of recording, classifying and summarizing business transactions conveys much more than simply the routine recording of business events in an accounting system, these activities would seem to be clearly in the realm of bookkeeping. Generally, an accounting system is designed to collect, classify and summarize business transactions, as well as business activities. An accounting system may be a manual system, a semi-mechanical system, or an electronic computer system. The study of the more recent developments in accounting systems, such as electronic systems, or computer systems, is especially interesting in regard to their potential in the area of analysis. Education for accounting must involve the study of all reasonable alternative systems, principles, standards and methods of measuring the effects of business activities. Accounting systems may be divided into two main types, financial accounting and administrative or managerial accounting.